Evaluating Strategies for E-Commerce Sites : A Malaysian Perspective - Sherlin, G. Subramaniam (2003)
An organisation needs to evaluate its strategy for e-commerce site constantly due to the dynamic nature of the Internet. Using the ‘AIPD’ model developed by Simeon, this research attempts to evaluate strategies for e-commerce site for Malaysian Internet banking environment. There are 10 commercial banks with Web presence in Malaysia and all of these banks were included in this study. An organisations’ e-commerce site is the interface that connects the business with the customers. The needs and expectations of the customers are always changing due to changes in the business environment. This needs and expectations must be recognised in order to stay competitive. As such, e-commerce strategy is a crucial part that needs constant evaluation and taken seriously by the organisations. The lack of study in domestic e-commerce site strategy evaluation has motivated this research. The evaluation was carried out using three experts. Results from the evaluation were then used to compare the results from Simeon’s findings. The result reveals that Malaysian commercial banks are following effective informing, positioning, and delivering strategies. The APD model is later used to identify strategies in the Malaysian Internet banking that needs improvement. This study reveals that technological advancement plays important role in Web site design and e-commerce strategy.